Can Historic Interiors with Large Cubature be Turned Acoustically Correct? - KAMISIŃSKI, Tadeusz Marek; KULOWSKI, Andrzej; KINASZ, Roman (Archives of Acoustics, 2016)
Historic interiors with large cubature, such as reception, theatrical, and concert halls, need to be renovated periodically if they are to be preserved as cultural heritage for future generations. In such cases it is necessary to maintain appropriate balance between requirements imposed by heritage conservation authorities office which are usually being given a higher priority, applicable safety regulations, and the comfort of use, including good acoustics.The paper is a presentation of architectural interference in three historic interiors with large cubature leading to changes in their acoustic qualities. In two cases, the changes were beneficial to the functional qualities of the halls to satisfaction of the investors carrying out the renovation work. In the third instance, the architectural interference aimed at showing off the monumental valor of the interior resulted in significant degradation of its acoustics. To remedy the situation impairing the functional program of the facility, corrective measures are proposed neutral with respect to its historic character.